PENGARUH TENAGA KERJA, INVESTASI, DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI KABUPATEN PADANG LAWAS - Ramadan Pasaribu; Maryam Batubara; Nur Ahmadi Bi Rahmani (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine the effect of labor, investment and economic growth on the level of poverty in Padang Lawas Regency. This type of research is library research. Research carried out using literature (library), both in the form of books, notes, and reports of previous research results. This study explores data sourced from data published by the Central Statistics Agency (BPS), BKPM (Investment Coordinating Board) and Manpower Office (employment office) Padang Lawas Regency. The results of the analysis in this study are: (1) Labor has a negative effect on the level of poverty in the district of Padang Lawas. (2) Investment has a negative effect on the level of poverty in the district of Padang Lawas. (3) Economic growth has a negative effect on the level of poverty in the district of Padang Lawas. (4) Labor, Investment and Economic Growth simultaneously or jointly have a significant effect on the poverty level. Keywords:Labor, Investment, Economic Growth and Level Poverty